Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data

Henri Lefebvre’s Theory of the Production of Space and the Critical Theory of Communication - Fuchs, Christian (Communication Theory)

Öffentlichkeit im digitalen Kapitalismus - Fuchs, Christian (Das Ende der Vielfalt? Zur Diversität der Medien)

Social Media, Big Data, and Critical Marketing - Fuchs, Christian (The Routledge Companion to Critical Marketing)

Appropriation of Digital Machines and Appropriation of Fixed Capital as the Real Appropriation of Social Being: Reflections on Toni Negri’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

M. N. Roy and the Frankfurt School: Socialist Humanism and the Critical Analysis of Communication, Culture, Technology, Fascism and Nationalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

What is Critical Digital Social Research? Five Reflections on the Study of Digital Society - Fuchs, Christian (Journal of Digital Social Research)

We Need a Full Public Service Internet – State-Owned Infrastructure is Just the Start - Fuchs, Christian (The Conversation)

Boris Johnson Takes His Brexit Demagoguery to the Social Media Sphere - Fuchs, Christian (TruthOut)

重读马克思:资本主义批判与激进理论的未来[J] - Fuchs, Christian; Monticelli, Lara (国外理论动态 (Foreign Theoretical Trends) 2019 (8))

Critical Theory of Communication: New Readings of Lukács, Adorno, Marcuse, Honneth and Habermas in the Age of the Internet (Chinese translation) - Fuchs, Christian

Revisiting the Althusser/E. P. Thompson-Controversy: Towards a Marxist Theory of Communication - Fuchs, Christian (Communication and the Public)

Straightforward Immobilization of Phosphonic Acids and Phosphoric Acid Esters on Mesoporous Silica and Their Application in an Asymmetric Aldol Reaction - Weinberger, Christian; Heckel, Tatjana; Schnippering, Patrick; Schmitz, Markus; Guo, Anpeng; Keil, Waldemar; Marsmann, Heinrich C.; Schmidt, Claudia; Tiemann, Michael; Wilhelm, René (Nanomaterials)
The combined benefits of moisture-stable phosphonic acids and mesoporous silica materials (SBA-15 and MCM-41) as large-surface-area solid supports offer new opportunities for several applications, such as catalysis or drug delivery. We present a comprehensive study of a straightforward synthesis method via direct immobilization of several phosphonic acids and phosphoric acid esters on various mesoporous silicas in a Dean–Stark apparatus with toluene as the solvent. Due to the utilization of azeotropic distillation, there was no need to dry phosphonic acids, phosphoric acid esters, solvents, or silicas prior to synthesis. In addition to modeling phosphonic acids, immobilization of the important biomolecule adenosine monophosphate (AMP) on the porous supports was also investigated. Due to the high surface area of the mesoporous silicas, a possible catalytic application based on immobilization of an organocatalyst for an asymmetric aldol reaction is discussed.

Phase Transitions of Ice in Aqueous Salt Solutions within Nanometer-Sized Pores - Jantsch, Evelyn; Weinberger, Christian; Tiemann, Michael; Koop, Thomas (The Journal of Physical Chemistry C)
We examined the effect of CaCl2 and LiCl on ice melting in mesoporous silica (MCM-41 and SBA-15 silica). For that purpose, we determined the ice melting temperature in pores of various size (pore radii between 1.9 and 11.1 nm) in water and aqueous solutions up to high total solute molality (up to about 12 mol kg–1) using differential scanning calorimetry. We found that both electrolytes reduce the ice melting temperature within the pores. An exception is the melting of ice in the smallest pores, which does not seem to be affected by the presence of solutes, most likely owing to an exclusion of the ions from entering the pores. For all other pores, we observed that the ice melting temperature decreases as a function of pore size and electrolyte concentration. Using thermodynamic considerations as well as additional experimental data we developed a parametrization that can be used to predict the ice melting point as a function of pore size and total solute molality. For that purpose, we extended a formulation of the effective water activity of aqueous solutions under mechanical pressure toward its application in confinement and tested this new parametrization on literature data.

Textile Transformationen: Die "Frau comme il faut" in der robe à transformation und die "Tempofrau" im Verwandlungskleid - Kraft, Kerstin

Laufsteg Museum. Über Modeausstellungen und Ausstellungsmoden - Kraft, Kerstin

Kulturelle Zyklographie der Dinge - Kraft, Kerstin

Phase Coupling of Bilateral Motor Areas Decreases from Bipedal to Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Abegail Louw, Quinette; Baumeister, Jochen

Social Media and Everyday Politics - Allmer, Thomas (Concept: The Journal of Contemporary Community Education Practice Theory)

Academic Labour, Digital Media and Capitalism - Allmer, Thomas (Critical Sociology)

Kritická teorie a sociální média: Mezi emancipací a komodifikací. Translated - Allmer, Thomas

Whitepaper Künstliche Intelligenz und Diskriminierung – Herausforderungen und Lösungsansätze - Matzner, Tobias; Beck, Susanne; Grundwald, Armin; Jacob, Kai (der Plattform Lernende Systeme)

Sinnvoll versus gesund? – Bestimmungen der Mediennutzung - Matzner, Tobias (Gehirn & Geist Nr. 1 (2019))

Plural, situated subjects in the critique of artificial intelligence - Matzner, Tobias (The Democratization of Artificial Intelligence – Net Politics in the Era of Learning Algorithms)

Challenging algorithmic profiling: The limits of data protection and anti-discrimination in responding to emergent discrimination - Mann, Monique; Matzner, Tobias (Big Data & Society)
The potential for biases being built into algorithms has been known for some time (e.g., Friedman and Nissenbaum, 1996), yet literature has only recently demonstrated the ways algorithmic profiling can result in social sorting and harm marginalised groups (e.g., Browne, 2015; Eubanks, 2018; Noble, 2018). We contend that with increased algorithmic complexity, biases will become more sophisticated and difficult to identify, control for, or contest. Our argument has four steps: first, we show how harnessing algorithms means that data gathered at a particular place and time relating to specific persons, can be used to build group models applied in different contexts to different persons. Thus, privacy and data protection rights, with their focus on individuals (Coll, 2014; Parsons, 2015), do not protect from the discriminatory potential of algorithmic profiling. Second, we explore the idea that anti-discrimination regulation may be more promising, but acknowledge limitations. Third, we argue that in order to harness anti-discrimination regulation, it needs to confront emergent forms of discrimination or risk creating new invisibilities, including invisibility from existing safeguards. Finally, we outline suggestions to address emergent forms of discrimination and exclusionary invisibilities via intersectional and post-colonial analysis.

Autonome Trolleys und andere Probleme. Konfigurationen Künstlicher Intelligenz in ethischen Debatten über selbstfahrende Kraftfahrzeuge - Matzner, Tobias (Zeitschrift für Medienwissenschaft)

Privatsphäre 4.0. Eine Neuverortung des Privaten im Zeitalter der Digitalisierung - Behrendt, Hauke; Loh, Wulf; Matzner, Tobias; Misselhorn, Catrin

Self-aligned organic thin-film transistors for flexible electronics - Meyers, Thorsten; Reker, Julia; Temme, Julian; Vidor, Fábio F.; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Inorganic p-channel thin-film transistors using CuO nanoparticles - Reker, Julia; Meyers, Thorsten; Vidor, Fábio F.; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Gas Responsive Nanoswitch: Copper Oxide Composite for Highly Selective H2S Detection - Paul, Andrej; Schwind, Bertram; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten (Advanced Functional Materials)
A nanocomposite material based on copper(II) oxide (CuO) and its utilization as a highly selective and stable gas-responsive electrical switch for hydrogen sulphide (H2S) detection is presented. The material can be applied as a sensitive layer for H2S monitoring, e.g., in biogas gas plants. CuO nanoparticles are embedded in a rigid, nanoporous silica (SiO2) matrix to form an electrical percolating network of low conducting CuO and, upon exposure to H2S, highly conducting copper(II) sulphide (CuS) particles. By steric hindrance due to the silica pore walls, the structure of the network is maintained even though the reversible reaction of CuO to CuS is accompanied by significant volume expansion. The conducting state of the percolating network can be controlled by a variety of parameters, such as temperature, electrode layout, and network topology of the porous silica matrix. The latter means that this new type of sensing material has a structure-encoded detection limit for H2S, which offers new application opportunities. The fabrication process of the mesoporous CuO@SiO2 composite as well as the sensor design and characteristics are described in detail. In addition, theoretical modeling of the percolation effect by Monte-Carlo simulations yields deeper insight into the underlying percolation mechanism and the observed response characteristics.

Nanoparticles and organic semiconductors for flexible electronics - Hilleringmann, Ulrich; Reker, Julia; Vidor, Fábio F.; Meyers, Thorsten; Joubert, Trudi H.; Bezuidenhout, Petroné (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Improved organic thin-film transistor performance by dielectric layer patterning - Temme, Julian; Meyers, Thorsten; Reker, Julia; Vidor, Fábio F.; Vollbrecht, Joachim; Kitzerow, Heinz; Paradies, Jan; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Mechanical deformation on nanoparticle-based thin-film transistors - Vidor, Fabio Fedrizzi; Meyers, Thorsten; Reker, Julia; Müller, Kathrin; Wirth, Gilson I.; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Oxygen detection with zinc oxide nanoparticle structures - Schwabe, Tobias; Balke, Axel; Bezuidenhout, Petrone; Reker, Julia; Meyers, Thorsten; Joubert, Trudi-Heleen; Hilleringmann, Ulrich (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Characterization of inkjet-printed dielectric on different substrates - Kruger, Jené; Bezuidenhout, Petroné H.; Hilleringmann, Ulrich; Joubert, Trudi-Heleen (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

Method of superposing a multiple driven magnetic field to minimize stray fields around the receiver for inductive wireless power transmission - Lange, Sven; Bueker, Maik-Julian; Sievers, Denis; Hedayat, Christian; Foerstner, Jens; Hilleringmann, Ulrich; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Characterization of H-field Probes regarding Unwanted Field Suppression using Different Calibration Structures - Schroeder, Dominik; Hangmann, Christian; Hedayat, Christian; Otto, Thomas; Hilleringmann, Ulrich (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Wireless power supply for a RFID based sensor platform - Schmidt, Marco; Petrov, Dmitry; Hedayat, Christian; Hilleringmann, Ulrich; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Characterization of inkjet-printed dielectric on different substrates - Kruger, Jené; Bezuidenhout, Petroné H.; Hilleringmann, Ulrich; Joubert, Trudi-Heleen (Fifth Conference on Sensors, MEMS, and Electro-Optic Systems)

RFID based sensor platform for industry 4.0 application - Petrov, Dmitry; Schmidt, Marco; Hilleringmann, Ulrich; Hedayat, Christian; Otto, Thomas (Smart Systems Integration; 13th International Conference and Exhibition on Integration Issues of Miniaturized Systems)

Devolopment, Production and post-processing of a topology optimized aircraft bracket - Klippstein, Sven Helge; Duchting, Anne; Reiher, Thomas; Hengsbach, F.; Menge, Dennis; Schmid, Hans-Joachim (30th Annual International Solid Freeform Fabrication Symposium)
Structural parts for aviation have very high demands on the development and production process. Therefore, the entire process must be considered in order to produce high-quality AM metal parts. In this case study, a conventional part was selected to be optimized for AM. The process presented includes component selection, design improvement with a novel approach for topology optimization based on the AMendate algorithm as basis of MSC Apex Generative Design,component production on a SLM 250 HL and post-processing including heat treatment and surface smoothing. With the topology optimization a weight reduction of ~60 % could be realized, whereby the stress distribution is more homogeneous. Furthermore, the challenges of support optimization and post-processing have to be addressed, in order to produce competitive parts.

Einfache Ermittlung von Schnellhärtungsparametern für elementar geklebte Strukturen - Ditter, Jan; Aubel, Tobias; Teutenberg, Dominik; Meschut, Gerson (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Joining of high strength aluminum alloys by refill friction stir spot welding (III-1854-18) - Schmal, Christopher; Meschut, Gerson; Buhl, Nico (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Zwei Betrachtungen von Sicherheit und Privatheit nach Snowden - Auerbach, Benedikt; Shnayien, Mary; Kiltz, Eike; Tuschling, Anna (Datenschutz und Datensicherheit - DuD)
Was verstehen wir heute, sechs Jahre nach den Snowden-Leaks, unter IT-Sicherheit und Privatheit in digitalen Kulturen? Dieser Frage gehen Benedikt Auerbach aus kryptographischer und Mary Shnayien aus medienwissenschaftlicher Perspektive nach. So beschäftigt sich Benedikt Auerbach mit dem Skalierungsverhalten kryptographischer Verfahren. Es beschreibt, inwiefern sich Angriffe auf einzelne Nutzerinnen und Nutzer des Verfahrens zugroßskaligen Angriffen auf zahlreiche Nutzerinnen und Nutzer übertragen lassen – ein für Massenüberwachung durch Geheimdienste relevantes Angriffsszenario. Mary Shnayien untersucht ausgehend von der weltweiten Cyberattacke WannaCry diskursanalytisch, wie IT-Sicherheit zum Forschungsgegenstand und -feld wurde, und welche Metaphern das Feld strukturieren.

History and Aesthetics of Progress Indicators [Edistymispalkkien historia ja estetiikka] - Raczkowski, Felix; Shnayien, Mary (Tekniikan Waiheita)

Transformation und Wandel der Beruflichen Integrationsförderung. Vom „Erfolgsmodell“ zum „Problemfall“. - Heisler, Dietmar (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Der Beitrag skizziert in einem historischen Exkurs zentrale Entwicklungslinien der beruflichen Benachteiligtenförderung. Es wird deutlich, dass gesellschaftliche Veränderungen zu einer deutlich kritischeren und pädagogisch reflektierten Sicht auf berufliche Fördermaßnahmen geführt haben.
Keywords: Benachteiligtenförderung; Transformation

Potentiale und Herausforderungen von multiprofessionellen Teams aus systemischer Perspektive. - Engemann, Mario; Aßmann, Sandra; Bührmann, Thorsten

Kooperation zwischen Schulen und außerschulischen Bildungspartnern. Eine empirische Untersuchung zu Potenzialen und Herausforderungen von multiprofessionellen Teams am Beispiel des Projektes ‚Lebenswelten aktiv gestalten‘ - Engemann, Mario

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Marita Jendrischewski: Carl Schmitz – Vom Webstuhl in die Namib. Die Lebensgeschichte eines bergischen Missionars, Remscheid 2018 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Jutta Krauß / Ulrich Kneise: Welterbe Wartburg. Porträt einer Tausendjährigen, Regensburg 2016 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Friedl Brunckhorst / Karl Weber (Hg.): Kaiser Wilhelm II. und seine Zeit, Regensburg 2016 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Schire Jaakow und Weihnachtsidylle. Zum 100. Todestag von Alfred Rose - Schroeter-Wittke, Harald (Praktische Theologie)

Das neue Evangelische Gesangbuch – eine Phantasie - Schroeter-Wittke, Harald (Liturgie und Kultur)

Go down, Moses! Zum 75. Todestag von Robert Nathaniel - Schroeter-Wittke, Harald (Praktische Theologie)

Tod-Verweigerung. Zum 75. Todestag von Viktor Ullmann - Schroeter-Wittke, Harald (Praktische Theologie)

Rilkes Stunden-Buch. Ein Triptychon – neu - Schroeter-Wittke, Harald (Praktische Theologie)

Antje Mickan / Thomas Klie / Peter A. Berger (Hg.): Räume zwischen Kunst und Religion. Sprechende Formen und religionshybride Praxis (Rerum Religionum. Arbeiten zur Religionskultur 1), Bielefeld 2019 - Schroeter-Wittke, Harald (Kunst und Kirche)

Larissa Eikermann / Stefanie Haupt / Roland Linde / Michael Zelle (Hgg.), Die Externsteine. Zwischen wissenschaftlicher Forschung und völkischer Deutung, Münster 2018 - Schroeter-Wittke, Harald (Jahrbuch für Westfälische Kirchengeschichte)

Holger Pyka: Protestantische Karnevalsrezeption und Transformationen konfessioneller Mentalität. Stuttgart 2018 - Schroeter-Wittke, Harald (Jahrbuch der Hessischen Kirchengeschichtlichen Vereinigung)

Ingo Reuter: Surfaces│Oberflächen: Haut │ Spiegel │ Kleidung │ Wasser │ Bildschirm │ Erde. Würzburg 2019 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Jürgen Bärsch / Reimund Haas (Hgg.), Christen an der Ruhr, Band 6, Münster 2018 - Schroeter-Wittke, Harald (Jahrbuch für Westfälische Kirchengeschichte)

schaut hin (Mk 6,38). Ein Blick auf das Leitwort für den 3. Ökumenischen Kirchentag 2021 in Frankfurt am Main - Schroeter-Wittke, Harald (Der Kirchentag. Das Magazin)

Peter Zimmerling / Wolfgang Ratzmann / Armin Kohnle (Hg.): Martin Luther als Praktischer Theologe, Leipzig 2017 - Schroeter-Wittke, Harald (Luther)

Elisabeth von Thadden: Die berührungslose Gesellschaft, München 2018 - Schroeter-Wittke, Harald (Wege zum Menschen)

Quasiparticle and excitonic effects in the optical response of KNbO3 - Schmidt, Falko; Riefer, Arthur; Schmidt, Wolf Gero; Schindlmayr, Arno; Imlau, Mirco; Dobener, Florian; Mengel, Nils; Chatterjee, Sangam; Sanna, Simone (Physical Review Materials)
The cubic, tetragonal, and orthorhombic phase of potassium niobate (KNbO3) are studied based on density-functional theory. Starting from the relaxed atomic geometries, we analyze the influence of self-energy corrections on the electronic band structure within the GW approximation. We find that quasiparticle shifts widen the direct (indirect) band gap by 1.21 (1.44), 1.58 (1.55), and 1.67 (1.64) eV for the cubic, tetragonal, and orthorhombic phase, respectively. By solving the Bethe-Salpeter equation, we obtain the linear dielectric function with excitonic and local-field effects, which turn out to be essential for good agreement with experimental data. From our results, we extract an exciton binding energy of 0.6, 0.5, and 0.5 eV for the cubic, tetragonal, and orthorhombic phase, respectively. Furthermore, we investigate the nonlinear second-harmonic generation (SHG) both theoretically and experimentally. The frequency-dependent second-order polarization tensor of orthorhombic KNbO3 is measured for incoming photon energies between 1.2 and 1.6 eV. In addition, calculations within the independent-(quasi)particle approximation are performed for the tetragonal and orthorhombic phase. The novel experimental data are in excellent agreement with the quasiparticle calculations and resolve persistent discrepancies between earlier experimental measurements and ab initio results reported in the literature.

Excited-state band mapping and momentum-resolved ultrafast population dynamics in In/Si(111) nanowires investigated with XUV-based time- and angle-resolved photoemission spectroscopy - Nicholson, C. W.; Puppin, M.; Lücke, A.; Gerstmann, Uwe; Krenz, Marvin; Schmidt, Wolf Gero; Rettig, L.; Ernstorfer, R.; Wolf, M. (Physical Review B)

Water Splitting Reaction at Polar Lithium Niobate Surfaces - Dues, Christof; Schmidt, Wolf Gero; Sanna, Simone (ACS Omega)

Mode-independent quantum entanglement for light - Sperling, Jan; Perez-Leija, Armando; Busch, Kurt; Silberhorn, Christine (Physical Review A)

Nonlinear integrated quantum electro-optic circuits - Luo, Kai-Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Science Advances)
An integrated chip with quantum state generation, active polarization manipulation, and precise time control is demonstrated.
Keywords: Multidisciplinary

Intensity-dependent degenerate and non-degenerate nonlinear optical absorption of direct-gap semiconductors - Hannes, Wolf-Rüdiger; Krauß-Kodytek, Laura; Ruppert, Claudia; Betz, Markus; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXIII)

Higher-order contributions and nonperturbative effects in the nondegenerate nonlinear optical absorption of semiconductors using a two-band model - Hannes, Wolf-Rüdiger; Meier, Torsten (Physical Review B)

Potassium titanyl phosphate (KTP) quasiparticle energies and optical response - Neufeld, Sergej; Bocchini, Adriana; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
The KTiOPO4 (KTP) band structure and dielectric function are calculated on various levels of theory starting from density-functional calculations. Within the independent-particle approximation an electronic transport gap of 2.97 eV is obtained that widens to about 5.23 eV when quasiparticle effects are included using the GW approximation. The optical response is shown to be strongly anisotropic due to (i) the slight asymmetry of the TiO6 octahedra in the (001) plane and (ii) their anisotropic distribution along the [001] and [100] directions. In addition, excitonic effects are very important: The solution of the Bethe–Salpeter equation indicates exciton binding energies of the order of 1.5 eV. Calculations that include both quasiparticle and excitonic effects are in good agreement with the measured reflectivity.

Integration von Sprach- und Fachlernen im Kontext chinesisch-deutscher Kooperationsstudiengänge am Beispiel des Maschinenbaustudiums an der Chinesisch-Deutschen Technischen Fakultät (CDTF, Qingdao/Paderborn) - Denzer, Vera; Didier, Andrea; Drumm, Sandra; Hambach, Dennis; Kaplinska-Zajontz, Marta; Noeke, Josef; Settinieri, Julia; Xi, Lin; Zhu, Hongyu (Informationen Deutsch als Fremdsprache)
Am Beispiel des chinesisch-deutschen Kooperationsstudiengangs Maschinenbau an der Chinesisch-Deutschen Technischen Fakultät in Qingdao (China) werden unter Rückgriff auf unterschiedliche im Rahmen formativer Evaluation erhobener Datensätze Möglichkeiten und Grenzen der Integration von Fach- und Sprachlernen sowie Optimierungsmöglichkeiten der Unterstützung des studienvorbereitenden und -begleitenden (Fach-)Spracherwerbs diskutiert.

Ein Beitrag zum stoffschlüssigen Fügen durch plastische Deformation: partielles Kaltpressschweißen durch inkrementelles Walzen - Schmidt, Hans Christian

Ein Beitrag zur Herstellung von hybriden Bauteilen mittels Reibdrücken - Lossen, Benjamin

Beyond Big Data Capitalism, Towards Dialectical Digital Modernity: Reflections on David Chandler’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Introduction: Big Data Capitalism – Politics, Activism, and Theory - Fuchs, Christian; Chandler, David (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Karl Marx in the Age of Big Data Capitalism - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Evidence submitted to the House of Commons-Environment, Food and Rural Affairs Committee’s Inquiry on Rural Broadband and Digital Only Services, published on 26 June 2019 - Fuchs, Christian; Michalis, Maria

Evidence submitted to the House of Commons-Environment, Food and Rural Affairs Committee’s Inquiry on Rural Broadband and Digital Only Services, published on 26 June 2019 - Fuchs, Christian; Michalis, Maria

Slow Media: How to Renew Debate in the Age of Digital Authoritarianism - Fuchs, Christian (The Conversation)

Henry A. Giroux and the Culture of Neoliberal Fascism - Fuchs, Christian (Los Angeles Review of Books)

Herbert Marcuse: Einige gesellschaftliche Folgen moderner Technologie - Fuchs, Christian (Zeitschrift für Didaktik der Philosophie und Ethik)

Anisotropic Water-Mediated Proton Conductivity in Large Iron(II) Metal–Organic Framework Single Crystals for Proton-Exchange Membrane Fuel Cells - Bunzen, Hana; Javed, Ali; Klawinski, Danielle; Lamp, Anton; Grzywa, Maciej; Kalytta-Mewes, Andreas; Tiemann, Michael; von Nidda, Hans-Albrecht Krug; Wagner, Thorsten; Volkmer, Dirk (ACS Applied Nano Materials)
Herein we present a new proton-conducting iron(II) metal–organic framework (MOF) of an unusual structure formed by chains of alternating bistriazolate-p-benzoquinone anions and iron(II) cations with four axially coordinated water molecules. These chains assemble via π–π stacking between the aromatic units to form a three-dimensional grid-like network with channel pores filled with water molecules. The material was structurally characterized by single-crystal XRD analysis, and its water and thermal stability was investigated. The proton conductivity was studied by impedance measurements on needle-like single crystals. A simple but efficient measurement setup consisting of interdigital electrodes was used. The influence of the crystal orientation, temperature, and humidity was investigated. The iron(II)-MOF showed the highest proton conductivity of 3.3·10–3 S cm–1 at 22 °C and 94% relative humidity. Contrary to most known structures, the conductivity in this material is controlled by chemical properties of the pore system rather than by grain boundaries. The presented material is the starting point for further tailoring the proton-conducting properties, independent of morphological features which could find potential applications as membrane materials in proton-exchange membrane fuel cells.

Copper Oxide/Silica Nanocomposites for Selective and Stable H2S Gas Detection - Paul, Andrej; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten (ACS Applied Nano Materials)
A composite material of copper oxide (CuO) dispersed in the nanopores of KIT-6 silica (SiO2) is used as a dosimetric sensor for the detection of hydrogen sulfide (H2S) gas in low parts per milion concentrations. The sensor principle is based on the reversible chemical conversion of CuO to CuS, which guarantees a high selectivity, and on the corresponding percolation-induced change in electronic conductance.

Sono una madre single. Non sento di poter essere competitiva quanto altri: esperienze di personale precario nelle università del Regno Unito. Translated by Gloria Dagnin - Allmer, Thomas (Studies in Communication Sciences)

Joining of blanks by cold pressure welding: Incremental rolling and strategies for surface activation and heat treatment - Schmidt, H.C.; Homberg, W.; Orive, A.G.; Grundmeier, G.; Duderija, B.; Hordych, I.; Herbst, S.; Nürnberger, F.; Maier, H.J. (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

The Human is Dead, Long Live the Algorithm!. Human-Algorithmic Ensembles and Liberal Subjectivity - Matzner, Tobias (Theory, Culture & Society)
The article analyzes the relation of humans and technology concerning so called ‘intelligent’ or ‘autonomous’ algorithms that are applied in everyday contexts but are far removed from any form of substantial artificial intelligence. In particular, the use of algorithms in surveillance and in architecture is discussed. These examples are structured by a particular combination of continuity and difference between humans and technology. The article provides a detailed analysis of boundary practices that establish continuity and oppositions between humans and information technology, referring to their exemplary depiction in movies. Both strands of boundary practices have the potential to challenge as well as sustain the position of the human as liberal, autonomous subject. Finally, it is shown how the particular combination of continuity and difference that structures the use of algorithms maintains the power of liberal, autonomous subject positions, while the shift of decisions to the algorithms seems to decenter the human.

Privacy - Matzner, Tobias; Ochs, Carsten (Internet Policy Review)

Mediale und soziale Bedingtheit der Subjekte des Privaten – ein Versuch mit Hannah Arendt - Matzner, Tobias (Privatsphäre 4.0. Eine Neuverortung des Privaten im Zeitalter der Digitalisierung)

Organic Self-Adaptable Real-Time Applications - Khaluf, Lial; Rammig, Franz-Josef

History and Aesthetics of Progress Indicators [Edistymispalkkien historia ja estetiikka] - Raczkowski, Felix; Shnayien, Marie-Luise (Tekniikan Waiheita)

Zwei Betrachtungen von Sicherheit und Privatheit nach Snowden - Auerbach, Benedikt; Shnayien, Marie-Luise; Kiltz, Eike; Tuschling, Anna (Datenschutz und Datensicherheit - DuD 43)

Determinant groups of Hermitian lattices over local fields - Kirschmer, Markus (Archiv der Mathematik)
We describe the determinants of the automorphism groups of Hermitian lattices over local fields. Using a result of G. Shimura, this yields an explicit method to compute the special genera in a given genus of Hermitian lattices over a number field.
Keywords: General Mathematics

Jesus-Transformation als Filmmusikkinderbibel. Mario Castelnuovo-Tedescos Klavierzyklus „Εὐαγγέλιον. La storia di Gesù, narrata ai Fanciulli in 28 piccoli pezzi per Piano“ (1949) - Schroeter-Wittke, Harald (Jesus-Transformationen)

Gott lässt sich nicht spotten! (Gal 6,7) Blasphemie als theologisches, strafrechtliches und (religions-)pädagogisches Thema. Eine evangelische Position - Schroeter-Wittke, Harald (Staat und Religion. Aspekte einer sensiblen Verhältnisbestimmung)

Vertrauens-Bildung in evangelische Übergänglichkeit. Eine Einführung in Gemeindekultur- und -medienpädagogik - Schroeter-Wittke, Harald; Fermor, Gotthard (Gemeindepädagogik)

David Danced. Musikalische Spurensuche zu einer populären Szene - Schroeter-Wittke, Harald (Davidfigur und Opfermotiv. Jüdisch-christliche Transformationen)

8. Sonntag nach Trinitatis (11.8.2019). Jes 2,1-5: Auf geht’s – Von Sehnsuchtsliedern und Rückenwind - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)